2021
DOI: 10.3390/w13040484
|View full text |Cite
|
Sign up to set email alerts
|

Nonstationary Ecological Instream Flow and Relevant Causes in the Huai River Basin, China

Abstract: Based on the daily precipitation data during 1960–2016 at 72 stations and the daily streamflow data during 1956–2016 at 7 hydrological stations in the Huai River Basin (HRB), China, eco-surplus and eco-deficit under influences of abrupt streamflow behaviors were analyzed using Flow Duration Curve (FDC). The relations between indicators of hydrological alteration (IHA) and ecological indicators (Shannon Index, SI) were quantified, investigating impacts of altered hydrological processes on the evaluations of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The commonly used technique to gain the changing knowledge of flood regimes is nonstationary flood frequency analysis [9,21]. Strupczewski et al [22][23][24] presented a nonstationary approach to at-site flood frequency analysis, in which the distribution parameters are represented as the functions of explanatory variables to explain the nonstationary hydrological series [25,26]. Stasinopoulos and Rigby proposed "Generalized Additive Models for Location, Scale and Shape" (GAMLSS), which is a powerful implement for nonstationary frequency analysis of time series [27].…”
Section: Introductionmentioning
confidence: 99%
“…The commonly used technique to gain the changing knowledge of flood regimes is nonstationary flood frequency analysis [9,21]. Strupczewski et al [22][23][24] presented a nonstationary approach to at-site flood frequency analysis, in which the distribution parameters are represented as the functions of explanatory variables to explain the nonstationary hydrological series [25,26]. Stasinopoulos and Rigby proposed "Generalized Additive Models for Location, Scale and Shape" (GAMLSS), which is a powerful implement for nonstationary frequency analysis of time series [27].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the papers evaluated the impact of climate change and human activities on watershed hydrological variables [7][8][9][10][11][12][13], which indicated that the influence of a changing environment on the water cycle has been of concerned to more researchers. Among these articles, the hydrological variability under climate change and human influence in the Wuding River Basin was investigated [7]; the result shows that climate change and human influence drive both evapotranspiration and runoff changes.…”
mentioning
confidence: 99%
“…The paper of Liu et al [9] came to the same conclusion in the Lancang River Basin. Meanwhile, Wen et al [10] quantified the contribution of climate change and human activities (charactered by land changes) on the ecological instream flow. The result shows that the changes of ecological instream flow are in good line with precipitation and are mainly influenced by land changes.…”
mentioning
confidence: 99%